2020
DOI: 10.5093/pi2020a10
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Teaching Profession: Examining the Role of Social Support, Engagement and Emotional Intelligence in Teachers’ Intentions to Quit

Abstract: In recent decades, accumulating research has highlighted teacher attrition as an alarming issue for policymakers and social and educational administrators, mainly due to the cost of mental health treatment for teachers, the increase in healthcare expenditure and, ultimately, a decrease in student learning (Craig, 2017). Recent data from several countries have shown that the number of teachers leaving the profession within the first five years is placed at between 8% and 50% (Kelly et al., 2019). For instance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 70 publications
(109 reference statements)
3
21
2
13
Order By: Relevance
“…Specifically, employees scoring low in both engagement and EI showed the highest scores in organizational deviance. This aligns with a recent study in which EI acted as a protective factor against teacher turnover (Mérida-López et al, 2020). In this work, those teachers experiencing low engagement, and scoring low in self-report ability EI reported higher turnover intentions than their counterparts with high EI levels.…”
Section: Emotional Intelligence Abilities As Moderatorssupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, employees scoring low in both engagement and EI showed the highest scores in organizational deviance. This aligns with a recent study in which EI acted as a protective factor against teacher turnover (Mérida-López et al, 2020). In this work, those teachers experiencing low engagement, and scoring low in self-report ability EI reported higher turnover intentions than their counterparts with high EI levels.…”
Section: Emotional Intelligence Abilities As Moderatorssupporting
confidence: 89%
“…Therefore, this study aims to gain insight into the interactive effects of teachers' work engagement and EI abilities for explaining life and job satisfaction. Based upon past empirical research and the current knowledge on the moderating role of EI (e.g., Côté, 2014;Mérida-López et al, 2020), our expectation is that levels of teachers' work engagement will be linked to life and job satisfaction, with the strength of these relationships depending on teachers' EI abilities. As such, it is expected that teachers reporting low levels of engagement do not necessarily exhibit low levels of life and job satisfaction, with this relationship being moderated by available personal resources such as EI abilities.…”
Section: Emotional Intelligence Abilities As Moderatorsmentioning
confidence: 99%
“…This research aimed to determine the mediator role of burnout in the relationship between EI and performance. In prior studies [19][20][21][22][23][24][25][26], EI has been independently tested, and results demonstrated that EI predicts a better performance. However, the current work offers a new perspective in understanding the role of burnout in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Those workers with higher emotional intelligence tend to be more successful [19,20], more productive [21,22], and less susceptible to perform counterproductive work behaviors [23]. Moreover, subjects with higher EI have shown more engagement than their colleagues [24], less burnout [25], and a lower intention to quit [26].…”
Section: Emotional Intelligence and Work Performancementioning
confidence: 99%
“…In line with the values regarding the Spanish version, Cronbach's alpha was 0.77 in this study (Extremera et al, 2018). Finally, turnover intention was assessed with the Occupational Withdrawal Intentions Scale (Hackett et al, 2001) comprising three items; Cronbach's alpha was 0.94 in line with previous studies with Spanish teacher samples (Mérida-López et al, 2020).…”
Section: Participants and Proceduresmentioning
confidence: 57%